(untitled) - Kerrod, Robin (World Almanac Library, 2005)
This book explores the many successes of the shuttle program, including the daring recovery and repair of satellites by space-walking astronauts, and examines the human and technological costs of its tragic failures.
Includes index.
Includes chronology.
Includes glossary.
Includes bibliography.
4-8
Accelerated Reader AR
Keywords: Space shuttles